Indonesian migrant workers' views on financial management strategies at the beginning of the Pandemic in Japan - Avina, Asa; Aryanto, Bayu (Universitas Dian Nuswantoro, 2022)
At the start of the COVID-19 pandemic in Japan, the study attempts to explain the perspectives of Indonesian migrant workers on personal financial management measures. This research method is a descriptive qualitative approach. The data source is the results of an Indonesian migrant worker survey conducted in Japan. Questionnaires will be used to collect data from November to December 2021. The sample for this study consisted of 16 respondents who met the criterion of being Indonesian migrant workers who had worked in Japan for at least one year. Based on the analysis of migrant workers' perceptions of monthly financial management strategies in the pandemic period is divided into 4 posts: (1) Post 1, 15% of migrant workers' earnings are utilized for good, such as sending money to their parents back home. (2) Post 2, 15% of the monthly pay is set aside for savings or investments. (3) Post 3, 50% of the remuneration is used to cover monthly living expenses. And (4) Post 4, 20 percent of the salary is used by workers for personal pleasure (lifestyle).